Technological Tools Used in the EFL Teaching in Indonesia - Bambang Yudi Cahyono (Indonesia Technology Enhanced Language Learning (iTELL) Association, 2024)
Nowadays, technology has developed tremendously, and various technological tools have been applied in education, more particularly in English as a foreign language (EFL) teaching. However, there has been no comprehensive report on the types of technological tools that have been used so far and how beneficial they have been. This article aims to review the development and application of technological tools by connecting them to the development of the stages of the World Wide Web, starting from Web 1.0 to Web 4.0 entailing Artificial Intelligence, and the outbreak of the Covid-19. The exploration of the varieties of the technological tools used in the EFL teaching will give insights to EFL teachers on the varieties of technological tools and their benefits for EFL teaching, especially in Indonesia. Reflecting upon the results of the exploration, it is suggested that EFL teachers consider any of the technological tools in their classrooms either for practical purposes or research.